2012
DOI: 10.1371/journal.pone.0052973
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Analyte Network Markers for Tumor Prognosis

Abstract: Deregulation of gene expression, a hallmark of cancer, is caused by both genetic and epigenetic mechanisms. The rapid accumulation of epigenome maps of various cancers suggests a new avenue of research, namely integrating epigenomic data with other types of omic data for cancer diagnosis, prognosis, and biomarker discovery. We introduce the MAPIT algorithm (Multi Analyte Pathway Inference Tool), to enable principled integration of epigenomic, transcriptomic, and protein interactome data. As a proof-of-principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…Briefly, this algorithm, which uses a greedy search method, identifies highly connected sub-networks using a novel graph theoretic measure, parametric local modularity [25,29]. …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, this algorithm, which uses a greedy search method, identifies highly connected sub-networks using a novel graph theoretic measure, parametric local modularity [25,29]. …”
Section: Methodsmentioning
confidence: 99%
“…The docking analysis revealed that Ile-36, Glu-37, Asp-38 and Ser-39 were involved in the interaction with the ligand [99]. In a study aimed at finding novel targets for globlastoma, use of bioinformatics tools led to the discovery of several novel genes related to the disease [100]. The study was also be to discover a regulatory feedback loop mediated by cyclin-dependent kinase 1 (CDK1) and WEE1.…”
Section: Mcodementioning
confidence: 99%
“…Prognostic inference is linked to advancement in medicine, and networks are increasingly providing support to such achievements (Kim et al., 2012); Wu and Stein, 2012; Shi et al., 2012; Li et al., 2010). Given patient groups and parameters specific to them, prognostic models should be selected to predict the future occurrence of outcomes.…”
Section: Clinical Applicationsmentioning
confidence: 99%